Ageism in job interviews: Discreet ways of building co-membership through age categorisation. (February 2023) - Previtali, Federica; Nikander, Pirjo; Ruusuvuori, Johanna
This article investigates how age categorisation and prejudicial use of age are mobilised in talk by job applicants during job interviews and how recruiters affiliate with these. The institutional goal of recruitment is to ensure an unbiased process and evaluation, nevertheless, ageism against older workers emerges as unchallenged and culturally acceptable in authentic job interviews. In line with the discursive psychology (DP) approach, the analysis focuses on -isms as discursively constructed and categories as resources to accomplish social actions. A case study is conducted based on video recordings of 24 real job interviews held at an Italian staffing agency and analysed through membership categorisation and conversation analysis. The analysis provides evidence of how job applicants resort to age co-membership with recruiters to achieve affiliation – or remedy misalignment – by complaining about older workers. The study contributes to DP's re-specification of prejudices as interactional practices and links microanalysis to macro phenomena, such as ageism, through categorisation practices.